1984
DOI: 10.1007/bf00395489
|View full text |Cite
|
Sign up to set email alerts
|

Typing of intermediate filaments in malignant fibrous pleural tumors

Abstract: We report two cases of a malignant fibrous pleural tumor, one of the localized type and one of the diffuse type. In both cases, typing of intermediate filaments by immunofluorescence microscopy showed that the tumor cells were positive for vimentin and negative for (cyto)keratin and desmin. This result supports the concept that malignant fibrous pleural tumors do not arise from the (cyto)keratin-positive pleural mesothelium but from the submesothelial fibrous tissue. Thus, instead of the usual term "malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…For example, it has been reported that cytokeratin is limited t o the surface mesothelial cells of the pleura and that the submesothelial cells fail to stain for this epithelial marker. 6 More recently, however, it has been suggested that in reactive states submesothelial cells that normally lack cytokeratin acquire this marker as they pr~liferate.~*~** We have sought to confirm or refute these conflicting reports by applying antibodies raised against vimentin and cytokeratin intermediate filaments to mesotheliomas of connective tissue type and reactive pleural conditions. At the same time, we have applied the same antibodies to localized fibrous tumours of the pleura, as this should provide information relevant to histogenesis as well as to diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that cytokeratin is limited t o the surface mesothelial cells of the pleura and that the submesothelial cells fail to stain for this epithelial marker. 6 More recently, however, it has been suggested that in reactive states submesothelial cells that normally lack cytokeratin acquire this marker as they pr~liferate.~*~** We have sought to confirm or refute these conflicting reports by applying antibodies raised against vimentin and cytokeratin intermediate filaments to mesotheliomas of connective tissue type and reactive pleural conditions. At the same time, we have applied the same antibodies to localized fibrous tumours of the pleura, as this should provide information relevant to histogenesis as well as to diagnosis.…”
Section: Introductionmentioning
confidence: 99%